Binary Nonlinearization for AKNS-KN Coupling System - Xiangrong Wang; Xiaoen Zhang; Peiyi Zhao (Abstract and Applied Analysis)
The AKNS-KN coupling system is obtained on the base of zero curvature equation by enlarging the spectral equation. Under the Bargmann symmetry constraint, the AKNS-KN coupling system is decomposed into two integrable Hamiltonian systems with the corresponding variables x, tn and the finite dimensional Hamiltonian systems are Liouville integrable.